Dynamics of Intergenerational Poverty Transfer: The Impact of Poverty Levels, Education Levels, and Minimum Wages in West Sumatra - Meriska Suwatri; Nasri Bachtiar (Transpublika Publisher, 2024)
Intergenerational poverty is a complex issue involving various factors, including education, unemployment, and minimum wages. This study analyzes the impact of education levels, unemployment rates, and minimum wages on poverty rates in West Sumatra using multiple linear regression models. Secondary data from the Central Statistics Agency (BPS) and the Ministry of Finance during the period of 2021-2023 were used to analyze 19 districts/cities in West Sumatra. The results indicate that education levels and minimum wages significantly affect the reduction of poverty rates, while unemployment rates contribute positively to increasing poverty. This study provides policy recommendations to enhance the quality of education and adjust minimum wages to break the intergenerational poverty cycle in the region.